Kinetics of Urea Desorption off Sulfuric Acid Treated Carbon as Slow Release Fertilizer - Rahayu, Theresia Evila Purwanti Sri; Amrullah, Shafwan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2019)
Urea is an important nitrogen source for plant but the price of urea fertilizer is relatively high. Urea uptake from urea manufacture waste water and its application as fertilizer is of high interest. The purpose of this study is to find out desorption ability of urea adsorbed porous carbon to be applied as fertilizer. Theoritically, urea released from porous carbon to environment has slower rate of mass transfer compare to conventional urea fertilizer because urea molecules in porous carbon has to pass through pores of carbon during its movement out of carbon. The porous carbon as adsorbent was made from coconut shell by pyrolysis, followed by sulfuric acid oxidation treatment Oxidation treatment carried out to extent adsorption capacity as well as to give additional sulfur nutrient when applied as fertilizer. Oxidation of carbon surface was performed using sulfuric acid (50%w) to soak porous carbon followed by heating at 90oC temperature for 2 hours. Desorption was conducted by placing porous carbon into beaker contain water and the raising of urea concentration in water recorded after 3,5,10, 30, and 60 minutes. Results reveal that the value of mass transfer coefficient (kc) and effective diffusivity (De) of urea desorption from porous carbon are 0,0293 – 0,0743 cm/s and 8 x 10-10 – 5 x 10-9 cm2/s with initial concentration of urea 1000, 2000, and 4000 mg/L. Release rate of urea from porous carbon and urea prill are 0,07 ppm/s and 1,23 ppm/s. Slower release rate of urea off porous carbon than urea prill shows the promising of urea recovery using porous carbon as slow release fertilizer.